Future Democracies - Laboratory of Collective Intelligence for Participatory Democracy - Yago Bermejo (MediaLab Prado, 2019)
The Laboratory of Collective Intelligence for Participatory Democracy (2016-2019) is a project that arose out of Medialab Prado in coordination with the Government Area of Citizen Participation, Transparency and Open Government of the city of Madrid. Its work has been very connected with the analysis, reflection and innovation found on the digital participation platform Decide Madrid. The project has also organised many workshops and conferences that have brought together hundreds of people from the world of participatory democracy. This publication summarises the project’s core working principles as well as the open activities it has hosted over the course of these three years. These pilot experiences offer a possible vision of the future of democratic governance.
Keywords: Democracy